A Regulatory Oversight Model for the Sale of Sex Toys: Protecting Adolescent Reproductive Health Rights in Indonesia - Mangesti, Yovita Arie; Suhartono, Slamet; Setyorini, Erny Herlin; Yuristasari, Cintya Agustina; Amelia, Mays; Sari, Nanda Kartika (Journal of Posthumanism, 2025)
The unregulated sale of sex toys in Indonesia poses a significant challenge to adolescent reproductive health rights and legal protection. Despite their growing availability, particularly through online platforms, there is a lack of specific legal frameworks to oversee their distribution. This research aims to develop a comprehensive regulatory oversight model that addresses legal, institutional, and educational dimensions to ensure the protection of adolescents. Employing a socio-legal research approach, the study analyzes Indonesian national laws and draws comparative insights from countries such as Germany and Japan. Findings reveal that the current legal ambiguity contributes to potential misuse and increased vulnerability among adolescents. The proposed model includes criminalization of unauthorized sales as pornography-related offenses, integration of comprehensive sex education into national curricula, empowerment of regulatory bodies for product certification, and the enforcement of strict e-commerce policies. This model offers a strategic response to contemporary health and legal challenges in safeguarding adolescent well-being in the digital age.